Definition, formation and rupture mechanisms of water pockets in alpine glaciers: Insights from an updated inventory for the Swiss Alps - Christophe Ogier; Mauro Fischer; Mauro A. Werder; Matthias Huss; Mauro Hupfer; Mylène Jacquemart; Olivier Gagliardini; Adrien Gilbert; Leo Hösli; Emmanuel Thibert; Christian Vincent; Daniel Farinotti (Journal of Glaciology)
The term ‘water pocket’ describes invisible en- and subglacial water reservoirs that can cause sudden glacial outburst floods. However, there is currently no consensus on its definition and the formation and rupture mechanisms of water pockets remain poorly understood. This study aims to understand the mechanisms behind water pocket outburst floods (WPOFs) from alpine glaciers by analyzing their spatial and temporal distribution, pre-event meteorological conditions and the glacio-geomorphic features of the glaciers from which the floods originate. To this end, we updated an inventory of known WPOFs in the Swiss Alps to 91 events from 37 individual glaciers. Most WPOFs occurred between June and September, likely linked to meltwater input. Meteorological data indicate anomalously high temperatures during the days preceding most events and heavy precipitation on 25% of days for which WPOFs occur, indicating that water pockets typically rupture during periods of high water input. We propose four mechanisms of water pocket formation: temporary subglacial channel blockage (which is the mechanism suggested most often for our inventory), hydraulic barriers, water-filled crevasses and accumulation of liquid water behind barriers of cold ice (thermal barriers). Overall, our analysis highlights the challenge of understanding WPOFs due to the subsurface nature of water pockets, emphasizing the need for field-based research to improve their detection and monitoring.